Programmable polymer light emitting transistors with ferroelectric polarization-enhanced channel current and light emission - Li, Xiaoran; Breemen, Albert J. J. M. van; Khikhlovskyi, Vsevolod; Smits, Edsger C. P.; Kemerink, Martijn; Broer, Dirk J.; Gelinck, Gerwin (Organic electronics, 2012)
We present a voltage programmable polymer light emitting field-effect transistor (LEFET), consisting of a green emitting polymer (F8BT), and a ferroelectric polymer, P(VDF-TrFE), as the gate dielectric. We show by both experimental observations and numerical modeling that, when the ferroelectric gate dielectric is polarized in opposite directions at the drain and source sides of the channel, respectively, both electron and hole currents are enhanced, resulting in more charge recombination and ∼10 times higher light emission in a ferroelectric LEFET, compared to the device with non-ferroelectric gate. As a result of the ferroelectric poling, our ferroelectric LEFETs exhibit repeated programmability in light emission, and an external quantum efficiency (EQE) of up to 1.06%. Numerical modeling reveals that the remnant polarization charge of the ferroelectric layer tends to ‘pin’ the position of the recombination zone, paving the way to integrate specific optical out-coupling structures in the channel of these devices to further increase the brightness.